The approach to UAV image acquisition and processing for very shallow water mapping - Paulina Kujawa; Jaroslaw Wajs; Krzysztof Pleśniak (International Journal of Applied Earth Observations and Geoinformation)
Shallow water areas need to be protected and continuously monitored as a habitat for diverse flora and fauna. These environments are subject to changes caused by both local phenomena, such as tides, and global phenomena, such as global warming. Efficient measurement techniques are needed to optimize the cost and time of data collection and processing. Equally important is to ensure that data processing achieves the highest possible accuracy, especially for depth measurements affected by refraction. The aim of this paper is to present several approaches to data processing, based on the availability of measurement instruments and programming skills, each offering different levels of accuracy. In this study, RGB images were collected from an unmanned aerial vehicle over a Polish lake, together with reference data from a single-beam echo-sounder and GNSS measurements of shallow water profiles. Several processing paths were proposed, including sun glint masking, photogrammetric processing, refraction correction, and the creation of three output models: a point cloud, DEM, and orthomosaic. The expected accuracies are discussed, along with recommendations for the best method, taking into account the strengths and limitations of each approach.